PENGUATAN EKSISTENSI MASYARAKAT HUKUM ADAT DITENGAH ARUS GLOBALISASI PASCA ERA INDUSTRI 4.0 - Nizam Zakka Arrizal; Samuel Dharma Putra Nainggolan; Mamay Komariah; Hezron Sabar Rotua Tinambunan; Jamalum Sinambela (SUPREMASI HUKUM, 2023)
Globalization brings us to a new order of life, because globalization is a process that takes place in people's lives with various kinds of progress and the rapid rise of capitalism. Of course legal products also develop in the era of globalization. The purpose of this study is to determine the development of madat law in the current era of globalization by using normative juridical methods. The results of this study indicate that the national cultural identity and customary rights of indigenous peoples are respected and protected as long as they do not contradict the principles of state law. Keywords: Globalization, Customary People, Customary Law, Industry 4.0